Management of Congenital Aural Atresia : A Case Report - Yuli Tetriana Sari; Delfitri Munir (Sumatera Medical Journal, 2019)
Congenital Aural Atresia (CAA) is the failure of development of the external auditory canal. It usually occurs in conjunction with microtia, which is malformation of the auricle due to the failure of development of the external ear. The evaluation and treatment of aural atresia present a number of challenges to the otologic surgeon. Computed tomography also plays a pivotal role in planning the surgery and grading the outcome of the surgery in congenital aural atresia. We report a case of unilateral congenital aural atresia and microtia and did a canalplasty and tympanoplasty in this patient.